Motivational Goal Bracketing with Non-rational Goals - Alexander K. Koch; Julia Nafziger (Institute of Labor Economics (IZA), 2021)
We provide a tractable model of motivational goal bracketing by a present-biased individual, extending previous work to show that the main insights from models with rational goals carry over to a setting with non-rational goals. Goals motivate because they serve as reference points that make substandard performance psychologically painful. A broad goal allows high performance in one task to compensate for low performance in the other. This partially insures against the risk of falling short of ones' goal(s), but creates incentives to shirk in one of the tasks. Narrow goals have a stronger motivational force and thus can be optimal, providing an explanation for observed instances of narrow bracketing. In particular, if one task outcome becomes known before working on the second task, narrow bracketing is always optimal.
Keywords: A12; C70; D91; 330; non-rational goals; multiple tasks; motivational bracketing; self-control